Study on the characteristics of alkali-activated fly ash-slag improved by cenosphere: Hydration and drying shrinkage. (3rd April 2023) - Ma, Hongqiang; Fu, Congcong; Huang, Kang; Dai, Enyang; Zhang, Shaochen; Fang, Youliang; Feng, Jingjing
Highlights: The addition of the cenosphere can accelerate the initial hydration rate of AAFS. High compressive strength (greater than80 MPa) can still be obtained by mixing 30% cenosphere. When the cenosphere content exceeds 20%, the drying shrinkage is reduced very significantly. The cenosphere content of 20% is suitable. Abstract: Cenosphere is coal-based solid waste material, which has similar chemical compositions to fly ash. In this paper, the effect of the cenosphere on hydration kinetics and drying shrinkage characteristics of AAFS pastes were explored, and the action mechanism of the cenosphere was deeply revealed. The results showed that the hydration induction period was prolonged, the hydration exothermic rate was reduced or the peak value was delayed during the acceleration period, and the 72 h hydration degree of the sample was increased when mixed with the cenosphere. The incorporation of more than 20% cenosphere significantly reduced the drying shrinkage of AAFS pastes. Comparing the results of compressive strength, drying shrinkage, and pore structure, the most suitable content of the cenosphere is 20%. To significantly improve the drying shrinkage of alkali-activated materials, the content can also be increased. The action mechanisms of the cenosphere are shown as the filling effect, pozzolanic activity, and surface effect. The addition of cenosphere reduces the amount of C-S-H, C-A-S-H and N-A-S-H gel phases, but increases the formation of silicates (calcium hydrosilitates and calcium hydroaluminates).